0196 Differences in Sleep Duration and Alertness Among Internal Medicine Interns Comparing Intensive Care Unit to General Medicine Rotations: A Secondary Analysis of the ICOMPARE Trial. (27th May 2020) - Cordoza, M; Basner, M; Asch, D A; Shea, J A; Bellini, L M; Carlin, M; Malone, S K; Desai, S V; Sternberg, A L; Tonascia, J; Volpp, K G; Mott, C G; et al.
Abstract: Introduction: Little is known about the impact of specific rotations on medical residents' sleep. The purpose of this analysis was to examine the difference in sleep duration and alertness among internal-medicine resident interns during intensive care unit (ICU) compared to general medicine (GM) rotations. Methods: This is a secondary report of a randomized non-inferiority trial of 63 United States internal-medicine residency programs. Programs were assigned to either standard duty-hour (80h workweek/16h shifts) or flexible (80h workweek/no shift-length limit) policies. Interns were followed for 2 weeks during either a GM or ICU rotation. The primary outcome was sleep duration/24h (actigraphy). Secondary outcomes were sleepiness (Karolinska Sleepiness Scale [KSS]) and alertness (number of Brief Psychomotor Vigilance Test [PVT-B] lapses). Data were averaged across days (thirteen 24-hour periods). Linear mixed-effect models with random program intercept were used to determine the association between each outcome by rotation, controlling for age, sex, and policy followed. Results: N=386 interns were included (mean age 27.9±2.1y, 194 (50.3%) males), with n=261 (67.6%) in GM, and n=125 (32.4%) in ICU. Average sleep duration was 7.00±0.08h and 6.84±0.10h for GM and ICU respectively (p=.09; 95%CI -0.02;0.33h). Percent of days with self-reports of excessive sleepiness were significantly more likely for ICU vs GM from 12am-6am (ICU: 20.2%; GM: 12.5%) and 6am-12pm (ICU: 20.5%; GM: 14.3%). GM had significantly more days with no excessive sleepiness (GM: 40.5%; ICU: 28.1%). Average KSS was 4.8±0.1 for both GM and ICU (p=.60; 95%CI -0.18;0.32). Average number of PVT-B lapses were 5.5±0.5 and 5.7±0.7 for GM and ICU respectively (p=.83; 95%CI -1.48;1.18 lapses). There were no significant differences in PVT-B response speed or false starts between rotations. Conclusion: Interns in ICU may experience more excessive sleepiness compared to GM interns, especially in early morning hours. However, sleep duration and alertness were not significantly different between rotations. Support: Funded by the National Heart, Lung, and Blood Institute and American Council for Graduate Medical Education